Factor influencing the distribution of product among Bumiputera entrepreneur in small medium industries at Malacca / Roszila Hashim - Hashim, Roszila (Faculty of Business and Management, 2009)
This research was conducted for the purposed of "Factor Influencing Distribution of Product among Bumiputera Entrepreneur at Malacca". The main objective of this research was to identify the factor that influencing product distribution in SMI which also can increase the number of distribution. The research is conducted using non-probability sampling and the sampling method is convenience sampling. The respondent of this research was Bumiputera Entrepreneur which is 40 respondents entrepreneur from Malacca. 50 questionnaires had been distributed to those Bumiputera Entrepreneur, but only 40 are valid and available. Factor influencing distribution of product such as transportation, cost, supplier and location play a major role in enhancing product distribution. Therefore these factors were used in this research. The conclusion of this research was the outcomes for the survey analysis and findings. Based on the finding, some recommendation have been suggested in order to help this industries increase their product distribution.